PANOPTICONS OF VIRTUAL IDENTITY ON WHATSAPP: SELF-ENCLOSURE OR SELF-ENCLOSING? - Priyadi, Rahkmat; Mubarok, Muhamad Husni (ASPIRATION Journal, 2023)
Profile photos on social media are meant to serve as a person's identity, but many people now choose not to use them especially for Y and Z generation. Ironically, they often hide their photos and sometimes replace their real names with fake ones. This phenomenon may seem trivial, but it raises significant questions. The aim of this research is to explore the factors of individuals decision to refrain from applying of profile photos among WhatsApp users. This is descriptive qualitative method with in-depth interviews conducted to the 13 informants. Michel Foucault's panopticon concept is used to demonstrate the absence of a WhatsApp profile photo. The findings indicate that individuals reasons’ can be divided into four motives: interpersonal conflict, avoiding social interactions, feeling surveillance by others, and self-discipline. A sense of surveillance from their social environment ultimately engaging in a type of self-regulation by removing their profile photo.